Escalating Number of Juvenile Delinquents in Barangay Bignay, Valenzuela City: An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Juvenile delinquency, or the involvement of minors in criminal behavior, is a pressing socialissue that poses challenges to communities worldwide. This study aims to assess theescalating number of juvenile delinquents in Barangay Bignay, Valenzuela City.The findings revealed the several risk factors contributing to the problem, including the familyenvironment of the child, peer pressure, and poverty; the problems encountered by therespondents in handling juvenile delinquents are the uncooperative parents. Additionally, theresearch highlighted the role of the community and its stakeholders, such as local governmentunits, law enforcement agencies, and social service providers, in addressing the issue ofjuvenile delinquency.Based on the assessment, recommendations for intervention and prevention strategies wereproposed, including implementing community-based programs that focus on addressing riskfactors, providing opportunities for education and skills development, and strengthening familysupport systeMs. The study underscores the need for collaborative efforts among variousstakeholders to effectively combat the rising cases of juvenile delinquency in Barangay Bignayand promote the well-being and rehabilitation of young offenders.
Keywords: Criminology